Slurry for tenon protection in aluminizing process and preparation and use methods thereof

During the smear of nickel-based single crystal high-temperature alloy blades, a multi-layer protective slurry is used to protect the tenon position, which solves the assembly problems caused by the coating and the reduction of mechanical properties, and achieves effective anti-seepage effects and easy removal.

CN119753566AActive Publication Date: 2025-04-04GUANGDONG INST OF NEW MATERIALS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411937774.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

During the aluminization process of nickel-based single crystal high-temperature alloy blades, the presence of the coating at the tenon head leads to an increase in geometric size, affecting assembly, and the coating is prone to notch, reducing mechanical properties, resulting in blade loss and failure.

Method used

A multi-layer protective slurry consisting of a bottom layer, a transition layer and a surface layer, including zirconium powder, zirconium oxide, NiAl powder and binder, is used to form an anti-seepage layer to protect the tenon position by coating and drying.

Benefits of technology

Effective protection of the tenon position is achieved, avoiding the surface forming an aluminized layer during the aluminized process, maintaining the geometric dimensions and mechanical properties of the blades, and the protective layer is easy to remove.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753566A_ABST
    Figure CN119753566A_ABST
Patent Text Reader

Abstract

The invention discloses slurry for tenon protection in the aluminizing process and a preparation and use method thereof. The anti-aluminum-seepage slurry comprises bottom layer protection slurry, transition layer protection slurry and surface layer protection slurry. Wherein the bottom layer protective slurry comprises the following components in parts by weight: 50-80 parts of zircon powder, 10-50 parts of a binder and 1-20 parts of deionized water; the transition layer protective slurry comprises the following components in parts by weight: 10-60 parts of zirconium oxide, 10-30 parts of a binder and 1-20 parts of deionized water; and the surface layer protective slurry comprises the following components in parts by weight: 10-30 parts of zirconium oxide, 10-40 parts of NiAl powder, 10-30 parts of a binder and 1-20 parts of deionized water. The three protective slurries are respectively and uniformly brushed on the surface of the blade tenon in sequence, and are dried at 70-200 DEG C for 20-60 minutes to form an anti-seepage aluminum protective layer, so that anti-seepage protection is provided for the blade tenon in the subsequent aluminizing process. The protective slurry disclosed by the invention is good in anti-seepage effect, low in cost, simple and convenient in preparation process, convenient to remove, free from reaction with a matrix alloy and high in applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-temperature alloy surface protection, and in particular to a slurry for tenon protection during aluminizing and a preparation and use method thereof. Background Art

[0002] Nickel-based single crystal high-temperature alloys are widely used in the manufacture of aircraft engine and gas turbine turbine blades due to their excellent high-temperature mechanical properties. Turbine blades are in harsh service environments and are usually subject to high-temperature oxidation and corrosion, which causes the high-temperature mechanical properties of the blades to deteriorate and reduces the service life of the blades. In order to ensure the high-temperature service performance of the blades and extend their service life, high-temperature protective coatings are usually applied to the blade surface for protection. Aluminide coatings and modified aluminide coatings are used for blade protection because of their good comprehensive resistance to high-temperature oxidation and corrosion.

[0003] However, in the process of preparing aluminide coating and modified aluminide coating on the blade surface, aluminizing is a key step that must be carried out in the preparation process. The tenon of the blade is a key position that bears high stress during service. Aluminizing the tenon will bring adverse effects: the presence of the coating at the tenon causes its geometric dimensions to increase, thereby affecting the assembly of the blade, resulting in the blade being unable to be installed and causing failure of the fit; the presence of the coating on the tenon surface is prone to produce sensitive notches, reducing the mechanical properties of the tenon and accelerating the loss and failure of the blade. Therefore, in order to ensure the performance of the blade, the tenon of the blade needs to be protected during the aluminizing process.

[0004] Applying slurry to the tenon is an effective protection method, but the current anti-seepage slurry formula is blocked by foreign technology, and the coating process is cumbersome and complicated to operate. There will be residues on the tenon after aluminizing, and the slurry is prone to cracking during high-temperature aluminizing. Therefore, there is an urgent need for a tenon protection slurry with good anti-seepage effect, low cost, simple preparation process, easy removal, and strong applicability. Summary of the invention

[0005] In view of this, the present invention provides a slurry for tenon protection during aluminizing and a preparation and use method thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A slurry for protecting tenons during aluminizing, consisting of the following three layers: a bottom layer protective slurry, a transition layer protective slurry and a surface layer protective slurry; wherein the bottom layer protective slurry comprises: zircon powder, a binder, and deionized water; the transition layer protective slurry comprises: zirconium oxide, a binder, and deionized water; the surface layer protective slurry comprises: zirconium oxide, NiAl powder, a binder, and deionized water.

[0008] Preferably, the weight proportions of the components of the base protective slurry are: 50-80 parts of zircon powder, 10-50 parts of binder, and 1-20 parts of deionized water; the weight proportions of the components of the transition layer protective slurry are: 10-60 parts of zirconium oxide, 10-30 parts of binder, and 1-20 parts of deionized water; the weight proportions of the components of the surface layer protective slurry are: 10-30 parts of zirconium oxide, 10-40 parts of NiAl powder, 10-30 parts of binder, and 1-20 parts of deionized water.

[0009] Preferably, the zircon powder is high-purity zircon powder with a particle size of 200-350 mesh; the zirconium oxide is high-purity zirconium oxide powder with a particle size of 10-20 μm; and the NiAl powder is high-purity NiAl powder with a particle size of 1-20 μm.

[0010] Preferably, the binder is at least one of polyvinyl alcohol, silica sol and sodium silicate.

[0011] A method for preparing a slurry for tenon protection during aluminizing, comprising the following steps:

[0012] According to the weight ratio of each component of the bottom protective slurry, zircon powder is measured to obtain bottom layer powder, and the bottom layer powder, a binder and deionized water are evenly mixed to obtain a bottom layer protective slurry;

[0013] According to the weight ratio of each component of the transition layer protective slurry, zirconium oxide powder is measured to obtain transition layer powder, and the transition layer powder, a binder, and deionized water are evenly mixed to obtain a transition layer protective slurry;

[0014] Zirconia powder and NiAl powder were mixed according to the weight proportion of each component of the surface protective slurry, and the powders were mixed with a stirrer for 30 minutes to obtain a uniformly mixed surface layer powder;

[0015] The surface layer mixed powder, binder and deionized water are uniformly mixed according to the weight proportion of each component of the surface layer protective slurry to obtain the surface layer protective slurry.

[0016] A method for using a slurry for tenon protection during aluminizing. Before aluminizing, the protective slurry is applied to a position that does not need aluminizing, such as the tenon position of a blade, to form an impermeable layer to protect the tenon position of the blade and prevent the formation of an aluminized layer on the surface during high-temperature aluminizing.

[0017] Preferably, the method comprises the following steps:

[0018] Use a brush to evenly apply the bottom protective slurry to the tenon surface to achieve full coverage of the tenon position and avoid applying it on the blade position, and then dry it;

[0019] Take out the dried blades, and use a brush to evenly apply the transition layer protective slurry on the surface of the blade tenon coated with the bottom layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry;

[0020] Take out the dried blades, and use a brush to evenly apply the surface protective slurry on the surface of the blade tenon coated with the transition layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry;

[0021] After the blade is dried, a protective slurry can be obtained which can provide effective protection to the tenon position during the aluminizing process and does not react with the matrix.

[0022] Preferably, the thickness of the bottom layer protective slurry is 5-10 mm, the thickness of the transition layer protective slurry is 10-20 mm, and the thickness of the surface layer protective slurry is 10-30 mm; after the aluminizing is completed, it can be removed by lightly tapping with a rubber hammer.

[0023] Preferably, the drying temperature is 70-200° C., and the drying time is 20-60 min.

[0024] Compared with the prior art, the present invention has achieved the following technical effects:

[0025] (1) The present invention selects materials with similar physical and chemical properties as slurry powder, which has a low thermal expansion coefficient and good bonding and matching between layers;

[0026] (2) The present invention adopts a multi-layer combination of a bottom layer, a transition layer, and a surface layer to form a multifunctional layer with good anti-seepage effect and easy removal at the blade tenon position, thereby providing effective protection for the blade tenon during the aluminizing process;

[0027] (3) The present invention can achieve effective protection of the tenon by preparing a bottom protective layer with high structural strength and no reaction with the substrate, and can provide good structural support for the subsequent transition layer and the anti-seepage layer structure of the surface layer;

[0028] (4) The protective slurry of the present invention has simple ingredients, low cost and is easy to prepare;

[0029] (5) The protective slurry of the present invention has good high-temperature stability and high structural strength. It can maintain a good structure after aluminum infiltration and has strong applicability and can be used on a variety of nickel-based high-temperature alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a cross-sectional morphology diagram of the tenon position of the first nickel-based single crystal high-temperature alloy blade after aluminizing and then undergoing the slurry protection treatment of the present invention;

[0031] Figure 2This is a cross-sectional morphology of the tenon position of the first type of nickel-based single crystal high-temperature alloy blade after aluminizing and then using other protection schemes;

[0032] Figure 3 This is a cross-sectional morphology of the tenon position of the second type of nickel-based single crystal high-temperature alloy blade after aluminizing and slurry protection treatment;

[0033] Figure 4 This is a cross-sectional morphology of the tenon position of the second type of nickel-based single crystal high-temperature alloy blade after aluminizing and then using other protection schemes. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The invention discloses a slurry for protecting tenons during aluminizing, which is composed of the following three layers: a bottom layer protective slurry, a transition layer protective slurry and a surface layer protective slurry; wherein the weight proportions of the components of the bottom layer protective slurry are: 50-80 parts of zircon powder, 10-50 parts of a binder and 1-20 parts of deionized water; the weight proportions of the components of the transition layer protective slurry are: 10-60 parts of zirconium oxide, 10-30 parts of a binder and 1-20 parts of deionized water; the weight proportions of the components of the surface layer protective slurry are: 10-30 parts of zirconium oxide, 10-40 parts of NiAl powder, 10-30 parts of a binder and 1-20 parts of deionized water.

[0036] Zircon powder is high-purity zircon powder with a particle size of 200-350 mesh;

[0037] Zirconia is high-purity zirconium oxide powder with a particle size of 10-20 μm;

[0038] NiAl powder is high-purity NiAl powder with a particle size of 1-20μm.

[0039] The binder is at least one of polyvinyl alcohol, silica sol and sodium silicate.

[0040] The present invention also discloses a method for preparing a slurry for protecting tenons during aluminizing, comprising the following steps:

[0041] According to the weight ratio of each component of the bottom protective slurry, zircon powder is measured to obtain bottom layer powder, and the bottom layer powder, a binder and deionized water are evenly mixed to obtain a bottom layer protective slurry;

[0042] According to the weight ratio of each component of the transition layer protective slurry, zirconium oxide powder is measured to obtain transition layer powder, and the transition layer powder, a binder, and deionized water are evenly mixed to obtain a transition layer protective slurry;

[0043] Zirconia powder and NiAl powder were mixed according to the weight proportion of each component of the surface protective slurry, and the powders were mixed with a stirrer for 30 minutes to obtain a uniformly mixed surface layer powder;

[0044] The surface layer mixed powder, binder and deionized water are uniformly mixed according to the weight proportion of each component of the surface layer protective slurry to obtain the surface layer protective slurry.

[0045] The present invention also discloses a method for using a slurry for protecting tenons during aluminizing. Before aluminizing, the protective slurry is applied to positions that do not require aluminizing, such as the tenons of blades, to form an impermeable layer to protect the tenons of the blades and prevent the formation of an aluminized layer on the surface during high-temperature aluminizing.

[0046] The following steps are involved:

[0047] Use a brush to evenly apply the bottom protective slurry to the tenon surface to achieve full coverage of the tenon position and avoid applying it on the blade position, and then dry it;

[0048] Take out the dried blades, and use a brush to evenly apply the transition layer protective slurry on the surface of the blade tenon coated with the bottom layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry;

[0049] Take out the dried blades, and use a brush to evenly apply the surface protective slurry on the surface of the blade tenon coated with the transition layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry;

[0050] After the blade is dried, a protective slurry can be obtained which can provide effective protection to the tenon position during the aluminizing process and does not react with the matrix.

[0051] The thickness of the bottom protective slurry is 5-10mm, the thickness of the transition layer protective slurry is 10-20mm, and the thickness of the surface layer protective slurry is 10-30mm; after the aluminizing is completed, it can be removed by lightly tapping with a rubber hammer.

[0052] The drying temperature is 70-200°C and the drying time is 20-60 minutes.

[0053] Embodiment 1:

[0054] The tenon of the first nickel-based single crystal high-temperature alloy blade is taken as the protection object, and the protective slurry of the present invention is used for aluminizing protection. The specific implementation steps are as follows:

[0055] Step 1, cleaning the surface of the blade tenon, ultrasonically cleaning the blade in alcohol and acetone for 20 minutes in sequence, and then drying it for later use;

[0056] Step 2, prepare mixed powders of the bottom layer, transition layer, and surface layer according to the proportion, wherein the bottom layer powder and weight proportion are: 60 parts of zircon powder; the transition layer powder and weight proportion are: 50 parts of zirconium oxide powder. The surface layer powder and weight proportion are: 20 parts of zirconium oxide powder and 30 parts of NiAl powder. The surface layer powder is mixed in a blender for 30 minutes to obtain a uniformly mixed surface layer powder;

[0057] Step 3, using polyvinyl alcohol as a binder, measuring 20 parts by weight of polyvinyl alcohol, adding 15 parts of deionized water, mixing evenly at 80° C., and mixing evenly with the bottom layer powder to obtain a bottom layer protective slurry;

[0058] Step 4, use a brush to evenly apply the slurry to the tenon position of the first nickel-based single crystal high-temperature alloy blade, ensure that the tenon position is completely covered, avoid applying it to the blade body position, and the coating thickness is about 10 mm. Then, place the blade in an oven and bake it at 150° C. for 40 minutes;

[0059] Step 5, using polyvinyl alcohol as a binder, measuring 20 parts by weight of polyvinyl alcohol, adding 15 parts of deionized water, mixing evenly at 80° C., and mixing evenly with the transition layer powder to obtain a transition layer protective slurry;

[0060] Step 6, take out the dried blade coated with the bottom protective slurry, and after cooling, use a brush to apply the transition layer protective slurry to ensure that the tenon position is completely covered and avoid coating the blade body position. The coating thickness is about 15 mm, and then the blade is placed in an oven at 100° C. for 30 minutes;

[0061] Step 7, using polyvinyl alcohol as a binder, measuring 20 parts by weight of polyvinyl alcohol, adding 15 parts of deionized water, mixing evenly at 80° C., and mixing evenly with the surface layer powder to obtain a surface layer protective slurry;

[0062] Step 8, take out the dried blade coated with the transition layer protective slurry, and after cooling, use a brush to apply the surface protective slurry to ensure that the tenon position is completely covered and avoid coating the blade body position. The coating thickness is about 20 mm, and then the blade is placed in an oven at 100° C. for 60 minutes; after cooling, an anti-seepage layer is obtained at the tenon position of the blade;

[0063] As a comparison, other solutions were used to protect the tenon position of another blade by coating it with slurry.

[0064] After the slurry coating is completed, the blade body is wiped clean with alcohol; then, the first nickel-based single crystal high-temperature alloy blade coated with protective slurry at the tenon position and the comparison blade are aluminized at 1040°C for 5 hours;

[0065] After aluminizing, the first nickel-based single crystal high-temperature alloy blade was taken out, and the protective slurry was removed using a rubber hammer and tweezers. Then, the blade was ultrasonically treated in alcohol and acetone for 20 minutes respectively, and then dried.

[0066] The cross-sectional morphology of the tenon position of the first nickel-based single crystal high-temperature alloy blade protected by this patent was characterized using a scanning electron microscope. The results are as follows: Figure 1 As shown, no obvious infiltration layer was observed at the tenon position of the first nickel-based single crystal high-temperature alloy blade, and the matrix maintained the nickel-based single crystal high-temperature alloy structure, indicating that the tenon was well protected and the protective slurry had a good anti-seepage effect; no slurry residue was found on the surface, indicating that the slurry of the present invention has good removability after high-temperature aluminum infiltration.

[0067] The cross-sectional morphology of the blade tenon position protected by other solutions is as follows Figure 2 As shown, it can be found that there are many residual slurry particles on the surface of the tenon, and the matrix has obvious degradation areas. This shows that the slurry of this patent has obvious anti-seepage effect and excellent performance.

[0068] Embodiment 2:

[0069] The tenon of the second nickel-based single crystal high-temperature alloy blade is taken as the protection object, and the protective slurry of the present invention is used for aluminizing protection. The specific implementation steps are as follows:

[0070] Step 1, cleaning the surface of the blade tenon, ultrasonically cleaning the blade in alcohol and acetone for 20 minutes in sequence, and then drying it for later use;

[0071] Step 2, prepare mixed powders of the bottom layer, transition layer, and surface layer according to the proportion, wherein the bottom layer powder and weight proportion are: 70 parts of zircon powder; the transition layer powder and weight proportion are: 40 parts of zirconium oxide powder. The surface layer powder and weight proportion are: 30 parts of zirconium oxide powder and 30 parts of NiAl powder. The surface layer powder is mixed in a blender for 30 minutes to obtain a uniformly mixed surface layer powder;

[0072] Step 3, using polyvinyl alcohol as a binder, measuring 15 parts by weight of polyvinyl alcohol, adding 15 parts of deionized water, mixing evenly at 80° C., and mixing evenly with the bottom layer powder to obtain a bottom layer protective slurry;

[0073] Step 4, use a brush to evenly apply the slurry to the tenon position of the second nickel-based single crystal high-temperature alloy blade, ensure that the tenon position is completely covered, avoid applying it to the blade body position, and the coating thickness is about 10 mm. Then, place the blade in an oven and bake it at 130° C. for 50 minutes;

[0074] Step 5, using silica sol as a binder, measuring 20 parts by weight of silica sol and mixing it with the transition layer powder, and adding 2 parts of deionized water, mixing evenly to obtain a transition layer protective slurry;

[0075] Step 6, take out the dried blade coated with the bottom protective slurry, and after cooling, use a brush to apply the transition layer protective slurry to ensure that the tenon position is completely covered and avoid coating the blade body position. The coating thickness is about 10 mm, and then the blade is placed in an oven at 100° C. for 40 minutes;

[0076] Step 7, using silica sol as a binder, measuring 20 parts by weight of silica sol and mixing it with the surface layer powder, and adding 2 parts of deionized water, mixing evenly to obtain a surface layer protective slurry;

[0077] Step 8: Take out the dried blade coated with the transition layer protective slurry, and use a brush to apply the surface protective slurry after cooling, ensuring that the tenon position is completely covered and avoiding coating on the blade body position, with a coating thickness of about 15 mm, and then place the blade in an oven at 90°C for 40 minutes; after cooling, an anti-seepage layer is obtained at the tenon position of the blade. For comparison, other schemes are used to apply slurry to the tenon position of another blade for protection.

[0078] After the slurry coating is completed, the blade body is wiped clean with alcohol; then, the second nickel-based single crystal high-temperature alloy blade and the comparison blade coated with protective slurry at the tenon position are aluminized at 1020°C for 5 hours.

[0079] After aluminizing treatment, the second nickel-based single crystal high-temperature alloy blade is taken out, and the protective slurry is removed using a rubber hammer and tweezers. It is then ultrasonically treated in alcohol and acetone for 20 minutes respectively, and then blown dry.

[0080] The cross-sectional morphology of the tenon position of the second nickel-based single crystal high-temperature alloy blade protected by this patent was characterized using a scanning electron microscope. The results are as follows: Figure 3 As shown, no obvious infiltration layer was observed at the tenon position of the second nickel-based single crystal high-temperature alloy blade, and the matrix maintained the nickel-based single crystal high-temperature alloy structure, indicating that the tenon was well protected and the protective slurry had a good anti-seepage effect. No slurry residue was found on the surface, indicating that the protective slurry of the present invention has good removability after high-temperature aluminization.

[0081] The cross-sectional morphology of the blade tenon position protected by other solutions is as follows Figure 4As shown, it can be found that there are more residual slurry particles on the surface of the tenon, and the matrix has obvious degradation areas. The slurry of this patent has obvious anti-seepage effect and excellent performance.

[0082] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A slurry for tenon protection during aluminizing, characterized in that: It is composed of the following three layers: a bottom layer protective slurry, a transition layer protective slurry and a surface layer protective slurry; wherein the bottom layer protective slurry includes: zircon powder, a binder, and deionized water; the transition layer protective slurry includes: zirconium oxide, a binder, and deionized water; the surface layer protective slurry includes: zirconium oxide, NiAl powder, a binder, and deionized water.

2. The slurry for tenon protection during aluminizing according to claim 1, characterized in that: The weight proportions of the components of the bottom layer protective slurry are: 50-80 parts of zircon powder, 10-50 parts of binder, and 1-20 parts of deionized water; the weight proportions of the components of the transition layer protective slurry are: 10-60 parts of zirconium oxide, 10-30 parts of binder, and 1-20 parts of deionized water; the weight proportions of the components of the surface layer protective slurry are: 10-30 parts of zirconium oxide, 10-40 parts of NiAl powder, 10-30 parts of binder, and 1-20 parts of deionized water.

3. The slurry for tenon protection during aluminizing according to claim 1, characterized in that: The zircon powder is high-purity zircon powder with a particle size of 200-350 mesh; the zirconium oxide is high-purity zirconium oxide powder with a particle size of 10-20 μm; and the NiAl powder is high-purity NiAl powder with a particle size of 1-20 μm.

4. The slurry for tenon protection during aluminizing according to claim 1, characterized in that: The binder is at least one of polyvinyl alcohol, silica sol and sodium silicate.

5. A method for preparing a slurry for tenon protection during aluminizing, characterized in that: The following steps are involved: According to the weight ratio of each component of the bottom protective slurry, zircon powder is measured to obtain bottom layer powder, and the bottom layer powder, a binder and deionized water are evenly mixed to obtain a bottom layer protective slurry; According to the weight ratio of each component of the transition layer protective slurry, zirconium oxide powder is measured to obtain transition layer powder, and the transition layer powder, a binder, and deionized water are evenly mixed to obtain a transition layer protective slurry; Zirconia powder and NiAl powder were mixed according to the weight proportion of each component of the surface protective slurry, and the powders were mixed with a stirrer for 30 minutes to obtain a uniformly mixed surface layer powder; The surface layer mixed powder, binder and deionized water are uniformly mixed according to the weight proportion of each component of the surface layer protective slurry to obtain the surface layer protective slurry.

6. A method for using a slurry for tenon protection during aluminizing, characterized in that: Before aluminizing, a protective slurry is applied to positions that do not require aluminizing, such as the tenon position of the blade, to form an anti-seepage layer to protect the tenon position of the blade and prevent the formation of an aluminizing layer on the surface during the high-temperature aluminizing process.

7. The method for using the slurry for tenon protection during aluminizing according to claim 6, characterized in that: The following steps are involved: Use a brush to evenly apply the bottom protective slurry to the tenon surface to achieve full coverage of the tenon position, avoid applying it on the blade position, and then dry it; Take out the dried blades, and use a brush to evenly apply the transition layer protective slurry on the surface of the blade tenon coated with the bottom layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry; Take out the dried blades, and use a brush to evenly apply the surface protective slurry on the surface of the blade tenon coated with the transition layer protective slurry to achieve full coverage of the tenon position, avoid coating on the blade position, and then dry; After the blade is dried, a protective slurry can be obtained which can provide effective protection to the tenon position during the aluminizing process and does not react with the matrix.

8. The method for using the slurry for tenon protection during aluminizing according to claim 6, characterized in that: The thickness of the bottom layer protective slurry is 5-10 mm, the thickness of the transition layer protective slurry is 10-20 mm, and the thickness of the surface layer protective slurry is 10-30 mm. After the aluminizing is completed, it can be removed by lightly tapping with a rubber hammer.

9. The method for using the slurry for tenon protection during aluminizing according to claim 6, characterized in that: The drying temperature is 70-200° C., and the drying time is 20-60 minutes.

Citation Information

Patent Citations

  • Masking material, masking layer, method for masking a substrate and method for coating a substrate

    CN102086503A

  • Anti-carburizing construction process for casting cooling water pipe in blast furnace cooling wall

    CN102367498A

  • Aluminized protective coating as well as preparation method and application thereof

    CN107267912A

  • Protective coating use method

    CN108970950A

  • Aluminum-chromium co-permeation protective coating and preparation method and application thereof

    CN110923621A